Revitalizing IoT-based air quality monitoring system for major cities in Indonesia - Kustija, Jaja; Fahrizal, Diki; Nasir, Muhamad (Universitas Mercu Buana, 2024)
An IoT-based air quality monitoring system is a technology that integrates with the internet to monitor and measure numerous air quality metrics in real-time. CO levels, dust particle levels, temperature, and humidity are the air quality characteristics that must be monitored. The air quality monitoring system in its current state requires further development, such as challenges to acquiring accurate and real-time data and difficulty in accessing reliable information. Poor air quality causes various health problems, respiratory, vision, heart disease, and even cancer. The development of air pollution producers continues to increase along with the number of oil-fueled vehicles, industries operated using petroleum-fueled engines, power plants that use energy from coal, gas and petroleum. This study presents an IoT-based air quality parameter monitoring system solution that is connected with the Blynk platform and can be accessible in real time, in an effort to assist the SDGs program, which is mandated by the global community through the UN. The research technique employed is Analysis, Design, Development, Implementation, and Evaluation. The study successfully presented an IoT-based air quality monitoring system connected with the Blynk platform, which showed great accuracy in measurement 94.34% (CO), 81.15% (dust), 99.14% (temperature), and 96.84% (humidity). These results advance urban air quality monitoring and inform sustainable technology development, contributing to environmental and health-related SDGs.